Limiting amino acids in milo for the growing pig - T E Eckert; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1973)
Three growth trials and two nitrogen retention trials were conducted with 118 growing pigs to determine the limiting amino acids in milo. Lysine supplementation of the basal milo diet markedly improved daily gain, feed efficiency, and nitrogen retention. Adding threonine to diets containing supplemental lysine or lysine and methionine increased daily gain and improved feed efficiency. Similarly nitrogen retention was increased by adding threonine to the basal milo diet supplemented with lysine. Supplementing the basal milo diet with methionine in the presence of lysine gave no beneficial response in two trials and markedly depressed growth in a third. Supplementing with nonessential amino acids (glycine and glutamic acid) in the presence of all other amino acids studied gave no beneficial response. These data demonstrate that lysine is the first-limiting, and threonine the second-limiting amino acid in milo protein for the growing pig and that methionine is not third-limitirrg. The data suggest that isoleucine is the third-limiting amino acid in milo protien.; Swine Day, Manhattan, KS, November, 1973
Keywords: Swine day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 203; Swine; Limiting amino acids; Milo; Growing pigs; Methionine; Threonine